Repo market functioning when the interest rate is low or negative - Jean-Sébastien Fontaine; James Hately; Adrian Walton (Bank of Canada, 2017)
This paper investigates how a low or negative overnight interest rate might affect the Canadian repo markets. The main conclusion is that the repo market for general collateral will continue to function effectively. However, changes to market conventions - such as the introduction of a charge for settlement fails - or other institutional changes may be required so that the repo market for specific collateral continues to support liquidity on the secondary market for government bonds. The historical experience shows that the special repo market in other jurisdictions can function effectively even if the overnight rate is negative. Closer examination suggests what specific circumstances can lead to persistent settlement fails in the specific collateral repo market. Specifically, the combination of (i) low or negative interest rates, (ii) large aggregate short positions in bonds, and (iii) economic or policy surprises may lead to persistent settlement fails.
Keywords: D4; G10; G12; 330; Financial markets; interest rates; market structure and pricing